Bis(phosphinite) with C2-Symmetric Axis; Effects on the Ruthenium(II)- Catalyzed Asymmetric Transfer Hydrogenation of Acetophenone Derivatives - Aydemir, Murat; Durap, Feyyaz; Kayan, Cezmi; Baysal, Akin; Turgut, Yılmaz (Synlett, 2012)
Chiral ruthenium catalyst systems generated in situ from [Ru(η6-p-cymene)(μ-Cl)Cl]2 complex and chiral C2-symmetric bis(phosphinite) ligands based on amino alcohol derivatives were employed in the asymmetric transfer hydrogenation of aromatic ketones to give the corresponding optically active alcohols in high yield. The best results were obtained in the [Ru(η6-p-cymene)(μ-Cl)Cl]2 and (2S)-2-[benzyl(2-{benzyl[(2S)-1-[(diphenylphosphanyl)oxy]-3-phenyl propan-2-yl]amino}ethyl)amino]-3-phenylpropyl diphenylphosphinite or (2R)-2-[benzyl(2-{benzyl[(2R)-1-[(diphenylphosphanyl)oxy]-3-phenylpropan-2-yl]amino}ethyl)amino]-3-phenylpropyl diphenylphosphinite catalytic systems, which gave enantioselectivities of up to 93% ee and 99% conversion.
Keywords: phosphinites; enantioselectivity; hydrogenation; homogeneous catalysis; ruthenium; ketones